2019
DOI: 10.3390/genes10010037
|View full text |Cite
|
Sign up to set email alerts
|

Nonclonal Chromosome Aberrations and Genome Chaos in Somatic and Germ Cells from Patients and Survivors of Hodgkin Lymphoma

Abstract: Anticancer regimens for Hodgkin lymphoma (HL) patients include highly genotoxic drugs that have been very successful in killing tumor cells and providing a 90% disease-free survival at five years. However, some of these treatments do not have a specific cell target, damaging both cancerous and normal cells. Thus, HL survivors have a high risk of developing new primary cancers, both hematologic and solid tumors, which have been related to treatment. Several studies have shown that after treatment, HL patients a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…Moreover, the relationship between micronuclei and different types of NCCAs in other human diseases need to be studies, as NCCAs are clearly linked to different diseases [92,93,94]. Equally important, how micronuclei play a role in the somatic mosaicism need more attention.…”
Section: New Challenges and Opportunities For Micronuclei Researchmentioning
confidence: 99%
“…Moreover, the relationship between micronuclei and different types of NCCAs in other human diseases need to be studies, as NCCAs are clearly linked to different diseases [92,93,94]. Equally important, how micronuclei play a role in the somatic mosaicism need more attention.…”
Section: New Challenges and Opportunities For Micronuclei Researchmentioning
confidence: 99%
“…It also played an essential role in development of genome theory, a genomic theory of inheritance and evolution [ 1 , 2 , 3 ] ( Box 1 ). There are many reasons why the importance of chromosomal instability becomes obvious within the current gene-centric world of molecular research: (1) chromosomal changes are overwhelmingly associated with cancers (both within the process of cancer evolution and as the end products) [ 4 , 5 , 6 , 7 ]; (2) karyotype coding, the spatial and topological coding of genes’ addresses within the nucleus, providing the physical platform of gene interaction networks, represents a new type of system inheritance which differs from gene-coded “parts inheritance” (thus it is the formation of a new karyotype that leads to the emergence of new genome systems) [ 8 , 9 ]; (3) macro-cellular evolution is driven by genome re-organization, while micro-cellular evolution is driven by gene mutation and/or epigenetic function [ 10 , 11 ]; (4) many previously characterized functions of cancer genes are in fact dependent on chromosomal instability or should be re-examined for the ignored involvement of CIN [ 12 , 13 ]; and (5) chromosomal instability can function as an effective biomarker with predictive and prognostic value in clinics, exceeding that of sequencing-based methodologies [ 14 , 15 , 16 , 17 , 18 ]. Perhaps one of the biggest hidden reasons for this shift is the research community’s response to the disappointing results of the gene-centric approach, which considers that cancer is a disease of gene mutations and promises to identify the few key common cancer gene mutations.…”
Section: Introductionmentioning
confidence: 99%
“…The increase of cells with NCCA and genomic chaos in the samples after treatment is evident and undoubtedly, their origin is complex and multifactorial. There is a large amount of bibliography that shows that the agents used in chemotherapy and radiotherapy in our patients are clearly genotoxic and induce CA in noncancerous cells; the genotoxicity is documented in different type of cells (for review, see Frias et al 2019), as well as in murine models without viral infections (Berno et al 2016). Thus, we concluded that the genotoxicity of anticancer treatment was a major player in the origin of cells with NCCA and genomic chaos that we observed.…”
mentioning
confidence: 99%